2007
DOI: 10.1136/adc.2006.098061
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on anti-ganglioside antibodies in childhood Guillain-Barre syndrome

Abstract: In some children with GBS, one can detect raised IgG against various gangliosides, similar to that in adults. A recent infection with C jejuni is markedly associated with the presence of these antibodies. However, in contrast with what has been reported in adults, in this study we were unable to show a negative effect of these findings on the clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
2
10
2
1
Order By: Relevance
“…The link between antiganglioside antibodies and axonal forms has been demonstrated in numerous studies. [13][14][15][16] One of our key findings is that the axonal form (AMAN or AMSAN) has a higher risk of long-term sequelae, consistent with other studies. 17,18 However, these results must be interpreted with caution because other studies 8,11,19,20 have shown that, although the axonal forms have a slower recovery period than the demyelinating forms, there was no long-term difference between the two groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The link between antiganglioside antibodies and axonal forms has been demonstrated in numerous studies. [13][14][15][16] One of our key findings is that the axonal form (AMAN or AMSAN) has a higher risk of long-term sequelae, consistent with other studies. 17,18 However, these results must be interpreted with caution because other studies 8,11,19,20 have shown that, although the axonal forms have a slower recovery period than the demyelinating forms, there was no long-term difference between the two groups.…”
Section: Discussionsupporting
confidence: 90%
“…In our cohort, we highlight a significant correlation between the presence of an axonal form and the presence of antiganglioside antibodies and, more specifically, with anti‐GM1 antibodies. The link between antiganglioside antibodies and axonal forms has been demonstrated in numerous studies …”
Section: Discussionmentioning
confidence: 91%
“…Children with GBS are presumed to have a faster and better recovery than adults, although the long‐term disability and impact of childhood GBS have not been well defined (Vajsar et al, ; Korinthenberg et al, ; Ortiz‐Corredor and Peña‐Preciado, ; Schessl et al, ; McGrogan et al, ; Rabie and Nevo, ) . Case series in children with GBS report symptoms of weakness, numbness, paresthesias, pain, dyscoordination, and fatigue (Vajsar et al, ; Korinthenberg et al, ; Rabie and Nevo, ) which may persist for months (Nagasawa et al, ) .…”
Section: Introductionmentioning
confidence: 99%
“…In a German study investigating antiganglioside antibodies in childhood GBS, no significant differences were found as compared with adult GBS. The overall lower detected prevalence of antibody positive cases (11%) is likely to represent the high cut-off level used to define a positive sample by ELISA [42], and highlights one of the pitfalls in comparing results from different laboratories.…”
Section: Clinical Seriesmentioning
confidence: 96%